Peran Identitas Sosial terhadap Perilaku Prososial pada Penggemar BTS Emerging Adult di Jakarta yang Bekerja - Alma Mediana; Maharani Ardi Putri; Aisyah Syihab (Jurnal Ilmiah Psikologi MIND SET, 2023)
This study aims to determine the role of social identity toward prosocial behavior among emerging adult BTS fans in Jakarta who work. There were 113 respondents who took part in the study using a convenience sampling technique. The measurement tools used in this study were the Prosocialness Scale for Adults with 16 items to measure prosocial behavior and the Social Identity Questionnaire with 12 items consisting of cognitive centrality, in-group affect, and in-group ties to measure social identity. This study uses multiple linear regression test to analyze the data in this study. The results of this study indicate that there is a significant role of social identity toward prosocial behavior simultaneously. In the multidimensional analysis of social identity, there is no significant role of the cognitive centrality dimension and in-group influence on prosocial behavior among emerging adult BTS fans in Jakarta who work, and there is a significant role of in-group ties dimension on prosocial behavior among emerging adult BTS fans in Jakarta who work. The results of this study are expected to provide useful suggestions for practitioners in social intervention field and entertainment practitioners who are involved in the group formation process.